Genetic and Shared-Environment Effects on Stature and Lifespan. A Study of Dutch Birth Cohorts (1785–1920) Based on Genealogies - Jan Kok (Historical Life Course Studies)
Historical demography is generally concerned with the changing economic, social and normative contexts of human behaviour and health outcomes. To most historical demographers, the 'genetic' component of behaviour and health is either unknown or assumed to be constant. However, several studies point at the shift over time in the relative importance of environment and genes: in periods and social groups with strong normative or economic constraints on behaviour, the 'genetic potential' is often not realized. Therefore, to some extent, the waning of environmental constraints on heritability plays a role in changes in demographic outcomes over time. Determining the relative importance of heritability versus shared environment in historical populations for which only genealogies are available poses a challenge. Kin may live in different periods, and in different cultural and social settings. This explorative paper analyses the association between heights of conscripted relatives, as well as their life span. I estimate how the associations are affected by respectively genetic relatedness, shared historical period and shared social and geographical environment. Furthermore, I make a distinction between kin related via the mother versus kin related via the father. All kinds of kin are involved in the analysis: (half, full and twin) brothers, fathers, grandfathers, uncles and cousins. The data consist of about 3,000 men culled from Texel island genealogies, which also include descendants of families who had left the island. Life span has a weak, but still discernible, genetic element. The heritability of height is much stronger, especially at age 19/20. The correlations of mother’s kin with her son's heights are stronger than those of her husband's kin. The analysis does not yield a consistent effect of a protective environment on kin correlations in either height or life span.